Impact of maximal power training with and without plyometric on speed endurance and upper body power of team handball players - Ethiraj, B.; Kamatchi, M. (Physical Education of Students, 2020)
Background and Study Aim: The aim of this research is to investigate the impact of maximal power training with and without plyometrics on speed endurance and upper body power of team handball players. Material and Methods: Sixty college level men team handball players were randomly selected from Coimbatore district as subjects. Their age ranged between 18 and 25 years. The selected subjects were divided into three equal groups consisting of twenty each. No attempt was made to equate the groups. Experimental group I (n = 20) underwent maximal power training with plyometrics (MPTWP), Experimental group II (n = 20) underwent maximal power training without plyometrics (MPTWOP) for a period of 12 weeks and group III (n = 20) acted as control group (CG), the subjects in control group were not engaged in any training programme other than their regular work. Data obtained were evaluated in SPSS package. Results: The F value revealed that the speed endurance and upper body power were significantly improved due to the influence of maximal power training with plyometrics. Conclusions: As a result, 12 weeks of maximal power training with plyometrics can be said to increase the speed endurance and upper body power of team handball players.